Suspected flunixin poisoning of a wild Eurasian Griffon Vulture from Spain. Issue 2 (9th October 2014) - Zorrilla, Irene; Martinez, Rosa; Taggart, Mark A.; Richards, Ngaio
Abstract Exposure to residues of the nonsteroidal anti‐inflammatory drug (NSAID) diclofenac present in livestock carcasses has caused extensive declines in 3 Gyps vulture species across Asia. The carcass of a wild Eurasian Griffon Vulture (Gyps fulvus) was found in 2012 on an Andalucian (Spain) game hunting reserve and examined forensically. The bird had severe visceral gout, a finding consistent with Gyps vultures from Asia that have been poisoned by diclofenac. Liver and kidney samples from this Eurasian Griffon Vulture contained elevated flunixin (an NSAID) levels (median = 2.70 and 6.50 mg/kg, respectively). This is the first reported case of a wild vulture being exposed to and apparently killed by an NSAID outside Asia. It is also the first reported instance of mortality in the wild resulting from environmental exposure to an NSAID other than diclofenac. Caso de Sospecha de Envenenamiento por Flunixin de un Buitre Leonado en España